Diagnostics of Cars’ Gas Supply Systems per Tightness Parameters as a Factor of Ensuring Fire Safety - Simonyan, A. R.; Balayan, R․ M.; Karapetyan, E․ G․; Shaghoyan, V. A. (ՀԱԱՀ հիմնադրամ)
In order to ensure fire and explosion safety during the operation of gas cylinder vehicles, the control and technical condition of the elements in the vehicle’s power system, particularly one of the most important types of operational verification – technical diagnostics of the vehicle through identifying relevant methods and means has been considered in the current article. It is recommended to install leak detectors with built-in gas flow control sensors in the design of the power supply system of a compressed gas vehicle, which will ensure the detection of gas leaks in the event of depressurization of the car’s gas equipment reducing the number of accidents.
Keywords: Agricultural Engineering